KEKERASAN DALAM PACARAN PADA REMAJA PUTRI DI TANGERANG - Erna Mesra Mesra; Salmah Salmah Salmah; Fauziah Fauziah Fauziah (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
Conceptually, the violence that occurs in many part of the world in various forms is indicative of abuse of power,gender inequality and domination. Datingviolence (DV) is any act of violence commited agninst the couple. Whether physical, sexual emotional and psychological peformed by unmarried couples currently a problem that is quite prominent in the world community. Dating Violence (DV) impacts that could result in physical, psychological or economic. DV is often the case after domestic violence. Goals : Get thetype of information that is experience by the victim, information about the internal and external of the victims, knowing how the process occurs in the victim.The study design is qualitative, case study approach by using indepth interview to the three (3) DV's victims in Tangerang. The results showed that, over all, the victims experienced with this type of psychological, physical, economic and sexual harassment. Internal factors which influence the occurance of which the knowledge and exposure to information of victims. External factors which influence the occurance of which the parenting patterns and relationships ornegative influence of peers. Suggestions : Parents run a variety of roles at home, as a mother or a father, as a teacher and a role as a children's friends. Health workers in collaboration with the school to conduct reproductive health education.